Dança moderna e pilates: um estudo sobre tradição, narração e prática pedagógica - Feijó, Marcia Gonzalez (2017)
This study tried, to investigate how the narrative in the pedagogical practice of Pilates’ method and modern dance can constitute an experience in the body and for the body. It was characterized as a research of qualitative approach, of participant’s narrative type, since both students and students were subjects of the study. The corporal practices were developed with academics of the first semester of bachelor course in Dance at the Federal University of Santa Maria, RS state, in the discipline of Technical Exercises I, that has inserted in its curricular content the Modern Dance. The following methodological procedures were adopted for the best use in class: divided into three moments. At first, it performed body preparations based on the principles of Pilates’ movements. Next, the students were pedagogically taught how to experience, identify and relate these principles from these bodily practices from the technique of Martha Graham’s school and, in the third moment, it was provided a space for dialogue about these experiences in the body. Subsequently, I described the pedagogical practices, emphasizing the narratives of the research participants. As a starting point, for discussing the approaches of the two focused traditions, comparisons were made between the principles of Pilates’ movement and Graham’s technique, as well as technical movements, in relation to Pilates’ exercises, crossed by didactic resources, in order to promote possibilities of experience in the body and for the body. The materiality that emerged from this practical theoretical application has been asserted that it is feasible to generate experience in the body and by means of the body conception and the approach chosen by the teacher.